How long does the volumizing effect of a Zingiber officinale‐based lip plumper last?. (5th December 2016) - Mazzarello, V.; Solinas, G.; Bandiera, P.; Pomponi, V.; Piu, G.; Ferrari, M.; Montella, A.
Abstract: Objective: Lip plumpers should enhance lip volume. It has been shown that no noticeable result was obtained after long term use of these products. The present study has been carried out to assess lip plumpers' short term effectiveness within 2 h from application. Methods: Effectiveness was assessed using non‐invasive techniques. The effect on vascularisation was analyzed with the Mexameter MX 16 ®, and the volume enhancing effect was assessed by anthropometric measures and profilometry analysis from 3D scanning electron microscope (SEM) images using Alicona's MEX software. Sixty female volunteers were recruited for the study and the measurements were taken 15, 30, 60, 90 and 120 min after product application. Results: Product application produced a statistically significant increase of lip vascularisation during the first 15 min, which stayed unchanged until the 30th min, then decreased in intensity. The volumizing effect was revealed by 3D profilometry analysis only, not by anthropological measurements. The use of 3D SEM images showed an increase of 0.50 mm in the protrusion of the lip vermilion (MHP parameter) during the first 15 min from product application. Conclusion: Results suggest that the lip plumper temporarily enhances vasodilation and increases lip volume. Abstract : 3D profile of skin surface on the upper lip vermilion zone. Images used to produce 3D reconstructions of lips, acquired observing controreplica in the SEM. Example of surface profile line created by MEX software.